Influence of urokinase gene-knockout in C57BL/6-PlautmI. IBugThisPlau6FDhu/GFDhu mice on growth factors in malignant melanoma - E. M. Frantsiyants; I. V. Kaplieva; I. V. Neskubina; V. A. Bandovkina; L. K. Trepitaki; E. I. Surikova; N. D. Cheryarina; L. A. Nemashkalova; N. S. Lesovaya (Исследования и практика в медицине, 2020)
Purpose of the study. Studying characteristics of the growth factor dynamics in the intact skin, tumors and perifocal tissues of melanoma in urokinase (uPA) gene-knockout mice.Materials and methods. The study included male and female С57 ВL/6 mice (n=47) and C57BL/6‑Plautm1.1BugThisPlauGFDhu/GFDhu mice with uPA gene-knockout (n=31). В16/F10 melanoma was transplanted subcutaneously at a dose of 0.5 mL (1:10 in normal saline). Intact mice of the same strain served as controls. Levels of VEGFA, VEGFC, sVEGFR1, sVEGFR3, IGF1, IGF2, TGFβ1 and FGF21 were determined by ELISA in the skin, tumor and perifocal tissues isolated on the 21st day of the tumor growth.Results. uPA gene-knockout inhibited the growth (mostly in females) and metastasis (predominantly in males) of melanoma in mice. Inhibition of the migration of malignant cells in males could be due to low levels of TGF-β1 compared to С57 ВL/6 mice: in the skin – by 5.0 times, in tumors – by 1.8 times and in perifocal tissues – by 6.1 times. In uPA gene-knockout females, lower levels of TGF-β1 were observed in tumors – by 1.4 times inhibited metastasis, but not completely, and solitary metastatic foci were registered in the lungs. Нigh levels of IGF1 in tissues of all uPA gene-knockout mice (males: in tumors by 1.4 times, in perifocal tissues by 2.6 times, in the skin by 3.6 times; females: in tumors by 2.6 times, in perifocal tissues by 25.0 times, in the skin by 13.9 times, compared to С57 ВL/6 mice) could maintain the metastatic phenotype of cancer cells (in females) or hiher proliferative activity of melanoma cells (in males). Lower levels of FGF‑21 in tumors (males – by 5.3 times, females – by 18.4 times), perifocal tissues (males – by 9.6 times, females – by 8,5 times) and skin (males – by 6.7 times, females – by 3.3 times) in uPA gene-knockout animals could be due to the IGF‑1 growth, as their reciprocal interaction is known. Interestingly, a significant, although lesser than in mice with a normal genotype, accumulation of VEGFA in melanoma tissues was observed: in males – in tumors by 44.9 times, in perifocal tissues by 6.8 times, in the skin by 2.4 times; in females – in tumors by 5.6 times, in perifocal tissues by 2.6 times, in the skin by 3.3 times, compared to the corresponding intact controls, due to the probable involvement of the uPA receptor (uPAR) in the implementation of VEGF-induced processes.Conclusion. Changing the activity of a system of some growth factors, uPA gene-knockout modifies melanoma metabolism by inhibiting its growth and eliminating or reducing its metastatic activity.